Waterhammer Analysis in Pump Discharge Lines Caused by Power Failure. - Arranz, Perlita M. (Philippine Engineering Journal)
The safe design of a pumping system requires a knowledge of the maximum pump or motor speed, the minimum and maximum pressures that may occur in the system during transient conditions specifically after power failure. Knowledge of the time at which the minimum head, maximum head, zero flow, zero pump speed and the maximum reverse flow occurs at the pump can be helpful for the proper design of discharge valve closure time and other waterhammer protection devices. This paper presents the theoretical background of the waterhammer equations and the different methods of solutions to this unsteady flow phenomena that occur in pipelines. It provides the head and discharge at any time after power failure of a specific point along the pipeline for given initial and boundary conditions.